Laparoscopic Evaluation of Tubal Factors in Case of Patients With Sub Fertility - Adhikary, Indrani; Banu, Jesmine; Sultana, Parveen; Chowdhury, ASM Alambir; Fatima, Parveen (Journal of Chittagong Medical College Teachers’ Association, 2012)
In this prospective study was carried out in the department of Obstetrics and Gynaecology (infertility) Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the period of September 2010 to February 2011. For this purpose total number of 80 female partner of subfertile couples undergoing laparoscopy in the above centre. Patients have been evaluated in the infertililty out patient department with the detailed history of both husband and wife and also evaluated clinically. Patient suffering from both primary and secondary subfertility have been included in this study with the inclusion criteria women age 20-40 years. Male partners having normal semen analysis. Female partner tried unsuccessfully for 1 year and female partner having any pelvic pathology suggest by history and physical examination. They are selected for the diagnostic laparoscopy. Laparoscopy findings will be carefully recorded and showing in primary subfertility normal looking 30 (55.5%), peritubal adhesion 8(14.8%), signs of endometriosis 10 (18.5%), hydrosalphinx 6(11.1%) and in secondary subfertility normal looking 10(38.5%), peritubal adhesion 4(15.4%), signs of endometriosis 4(15.4%), hydrosalphinx 8(30.8%). In this study normal looking fallopian tube is more common in primary subfertility and hydrosalphinx is more common in secondary subfertility. Laparoscopic evaluation of fallopian tube among the patient with primary subfertility showing the condition of the fimbria normal looking 50 (92.6%), indrowing 2(3.7%), not visualized fimbria 2(3.7%) and in secondary subfertility normal looking 18(69.2%), indrowing 6 (23.1%), not visualized fimbria 2(7.7%). Fimbria normal looking more in primary subfertility and indrawing more in secondary subfertility. In peritubal adhesion 34pt among them 30(88.2%) are dye test negative. In endometriosis 30 patients among them 12(40%) are dye test negative. In pulmonary TB, salphingitis and ectopic pregnancy (100%) are dye test negative. In tubal patency test of the study patients were observed in case of primary and secondary subfertility. In primary subfertility both tube patent 24(44.4%), unilateral block 20(37%) and bilateral block 10 (18.5%) and in secondary subfertility both tube patent 12 (46.2%), unilateral block 8 (30.8%), bilateral block 6 (23.1%). Bilateral block more in secondary subfertility. No difference in case of both tube patent. JCMCTA 2012; 23(1): 17-20